Chemical Composition of Industrial Wood Waste and the Possibility of its Management - Malinowski, Ryszard; Meller, Edward; Ochman, Ireneusz; Malinowska, Katarzyna; Figiel-Kroczyńska, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Organic wood waste (sawdust, shavings, pieces of wood and bark), is widely used as a secondary raw material and, after composting, for soil fertilisation and substrate production in agriculture, horticulture, forestry, urban landscaping and rehabilitation of degraded land. However, problematic to process is wood waste that is very dirty with soil. They have limited calorific value and cannot be used in the R10 recovery process of land treatment benefiting agriculture or improving the environment.
Keywords: wood waste; biomass; ash; chemical composition; fertilizer value; agricultural use; soil reclamation; odpady drzewne; biomasa; popiół; skład chemiczny; wartość nawozowa; wykorzystanie rolnicze; rekultywacja gleb